2021
DOI: 10.1161/jaha.120.021765
|View full text |Cite|
|
Sign up to set email alerts
|

Thromboprophylaxis for Children Post‐Fontan Procedure: Insights From the UNIVERSE Study

Abstract: Background Patients with single‐ventricle physiology who undergo the Fontan procedure are at risk for thrombotic events associated with significant morbidity and mortality. The UNIVERSE Study evaluated the efficacy and safety of a novel liquid rivaroxaban formulation, using a body weight–adjusted dosing regimen, versus acetylsalicylic acid (ASA) in children post‐Fontan. Methods and Results The UNIVERSE Study was a randomized, multicenter, 2‐part, open‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
0
44
0
1
Order By: Relevance
“…For the evaluation of the efficacy and safety of pediatric DOACs and thus for the implementation of the PIPs 34 of the EMA mentioned at the beginning, there were three large, multinational, and thus multicenter studies: the DIVERSITY trial for dabigatran 35 and the EINSTEIN and the UNIVERSE trials for rivaroxaban. 34,36 In addition, there was also a single-arm phase III study assessing dabigatran for extended secondary venous thromboembolism (VTE) prevention. 37 In further DOACs studies they identified, Branstetter et al counted 16 neonates, 152 non-neonatal infants (>30 days to <2 years), 351 children, and 488 adolescents.…”
Section: Results Of Current Pediatric Trials On Doacsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the evaluation of the efficacy and safety of pediatric DOACs and thus for the implementation of the PIPs 34 of the EMA mentioned at the beginning, there were three large, multinational, and thus multicenter studies: the DIVERSITY trial for dabigatran 35 and the EINSTEIN and the UNIVERSE trials for rivaroxaban. 34,36 In addition, there was also a single-arm phase III study assessing dabigatran for extended secondary venous thromboembolism (VTE) prevention. 37 In further DOACs studies they identified, Branstetter et al counted 16 neonates, 152 non-neonatal infants (>30 days to <2 years), 351 children, and 488 adolescents.…”
Section: Results Of Current Pediatric Trials On Doacsmentioning
confidence: 99%
“…In all three trials, there were two types of endpoints: primary endpoints on the efficacy of the two DOACs compared with standard therapy and secondary endpoints related to adverse effects and the need for therapy adjustments. 35,36,39 The DIVERSITY and EINSTEIN trials were in children with acute VTE, and the UNIVERSE trial was in children post Fontan procedure.…”
Section: Results Of Current Pediatric Trials On Doacsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UNIVERSE study compared thromboprophylaxis with rivaroxaban or aspirin in 112 children post-Fontan surgery and revealed that patients who received rivaroxaban had a similar safety profile to those who received aspirin. A lower thrombotic event rate was also observed in the rivaroxaban group (2% vs. 9%) however this difference was statistically insignificant ( 76 ).…”
Section: Thromboprophylaxis In the Fontan Populationmentioning
confidence: 99%